2009
DOI: 10.1088/1758-5082/1/3/035002
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided design of microvasculature systems for use in vascular scaffold production

Abstract: In vitro biomedical engineering of intact, functional vascular networks, which include capillary structures, is a prerequisite for adequate vascular scaffold production. Capillary structures are necessary since they provide the elements and compounds for the growth, function and maintenance of 3D tissue structures. Computer-aided modeling of stereolithographic (STL) micro-computer tomographic (micro-CT) 3D models is a technique that enables us to mimic the design of vascular tree systems containing capillary b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…Bioprinting models, like models used in conventional rapid prototyping, are often converted to the STereoLithography (STL) file format as an intermediate between model and print path generation (Mironov et al 2009; Mondy et al 2009). These files contain accurate surface information of complex 3D geometries, and can be designed via graphic user interfaces, or created from clinical images, including those from Magnetic Resonance Imaging (MRI) and Computed Tomography (CT) (Keriquel et al 2010; Arai et al 2011).…”
Section: Bioprinting Techniquesmentioning
confidence: 99%
“…Bioprinting models, like models used in conventional rapid prototyping, are often converted to the STereoLithography (STL) file format as an intermediate between model and print path generation (Mironov et al 2009; Mondy et al 2009). These files contain accurate surface information of complex 3D geometries, and can be designed via graphic user interfaces, or created from clinical images, including those from Magnetic Resonance Imaging (MRI) and Computed Tomography (CT) (Keriquel et al 2010; Arai et al 2011).…”
Section: Bioprinting Techniquesmentioning
confidence: 99%
“…Bioprinting technology, on the other hand, currently does not allow multiscale tissue fabrication, where bifurcated vessels are required to be manufactured with capillaries to mimic natural vas cular anatomy. Although several researchers have investigated developing vascular trees using computer models [16], only a few attempts have been made toward fabricating bifurcated or branched channels [17]. Successful maturation toward functional mechanically integrated bifurcated blood vessel network is still a challenge.…”
Section: Hybrid Fabrication Of 3d Perfusable Tissuesmentioning
confidence: 99%
“…It has been reported that cardiac muscle tissue containing vessel-like structure was obtained from endothelial cells through tissue culture [31]. Fabrication of functional 3D tissues containing blood vessels is still a great challenge faced by 3D bio-printing [97].…”
Section: The Future Of 3d Bio-printingmentioning
confidence: 99%